WORK DISCIPLINE, WORK ABILITY AND WORK SUPERVISION ON THE EFFECTIVENESS OF EMPLOYEE WORK - Sumarno (PT. Berkah Digital Teknologi, 2022)
Purpose: This research is to find out and test how much influence the work discipline, work ability and work supervision on employee work effectiveness Research Methodology: The method used in this study is a descriptive verification survey. In this study, data and information were collected from respondents using a questionnaire. In this study, the population was employees of the Secretariat of the Office of Public Works and Spatial Planning (DPUPR). In this study, the sampling used a random sample (random sampling). While the sampling technique used total sampling, which means taking the entire existing population, by taking a sample of 40 employees of the Secretariat of the Office of Public Works and Spatial Planning (DPUPR).. Results: The study found that work discipline, work ability, and work supervision have a strong, moderate, and strong effect on employee work effectiveness respectively. Also, when work discipline and work ability are considered together, the effect on employee work effectiveness is very strong. Limitations: The study only used a sample of 40 employees from one specific organization, and the findings may not be generalizable to other populations or organizations. The study did not consider other possible factors that may influence employee work effectiveness, such as job characteristics or organizational culture Contribution: This study contributes to the fields of organizational behavior and human resource management by providing evidence of the importance of work discipline, work ability, and work supervision in determining employee work effectiveness. The findings of this study can be useful for managers and human resource professionals in designing and implementing policies and practices that support employee work effectiveness. Additionally, this study can be useful for future researchers in identifying areas for further research in this field.